Immune cell profiling reveals expanded stem cell–like memory T cells in anti-GAD65-associated neurological syndromes - Sumanta Barman; Martijn van Duijn; Madeleine Scharf; Marisol Herrera-Rivero; Paul Disse; Lara-Maria Preuth; Valeria Gulyaeva; Ilja Schwan; Eliza vom Stein; Michael Heming; Louisa Müller-Miny; Manuela Paunovic; et al. (Proceedings of the National Academy of Sciences, 2026)
The immunopathogenesis of autoimmune neurological syndromes (AINS) with antibodies against the 65 kDa isoform of glutamic acid decarboxylase (anti-GAD65 AINS) remains poorly understood. To elucidate underlying disease mechanisms and identify relevant cell populations, we performed single-cell RNA and immune repertoire sequencing of cerebrospinal fluid (CSF) and peripheral blood mononuclear cells (PBMCs) of eight anti-GAD65 AINS individuals compared to eight noninflammatory controls. In addition, PBMCs from 19 anti-GAD65 AINS individuals and 20 healthy controls were analyzed by multidimensional flow cytometry, and brain tissue specimens from four anti-GAD65 AINS individuals were examined histologically. We detected higher frequencies of stem cell–like memory T cells (TSCM) within the PBMCs and a marked enrichment and clonal expansion of activated CD4 + TSCM in the CSF of anti-GAD65 AINS individuals. Expanded T cells exhibited increased expression of proinflammatory genes. Histological analyses confirmed intraparenchymal CD8 + TSCM in three of four anti-GAD65 AINS individuals and rare meningeal/intraparenchymal CD4 + TSCM in one person. Although CSF B cell receptors (BCRs) displayed little to no clonal expansion, recombinant expression of 40 CSF BCRs revealed that 25% were GAD65-reactive with increased somatic hypermutations compared to non-GAD65-reactive BCRs. These findings further support the concept of an antigen-specific intrathecal immune response. In summary, we characterize the immune landscape of anti-GAD65 AINS at single-cell resolution and identify clonally expanded TSCM with cytotoxic properties as a hallmark of this disease.